18.2k views
1 vote
What is the solution to this Logarithmic Equation?

(Those are L's infront of the N)
ln x + ln x = 0

User Dpassage
by
4.5k points

2 Answers

2 votes

Answer:

x = 1

Explanation:

ln x + ln x = 0

2ln x = 0

ln x = 0

recall ln x =
log_(e)x

so equation becomes


log_(e)x = 0

or
e^(0)=x

since anything raised to the power of zero = 1

x = 1

User Samball
by
5.0k points
4 votes

Answer:

x = 1

Explanation:

We are to find the solution of the following logarithmic equation:


ln ( x ) + l n ( x ) = 0

We will add the similar elements to get:


2 l n ( x ) = 0

Dividing both sides by 2 and simplify to get:


\frac { 2 l n ( x ) } { 2 } = \frac { 0 } { 2 }


ln(x)=0

Applying the rule
a=log_b(b^a) to get:


0=ln(e^0)=ln(1)


ln(x)=ln(1)

Here the logs have the same base, so:

x = 1

User Reasurria
by
4.6k points